Pengaruh Manajemen Keuangan Terhadap Kinerja UMKM pada Usaha Kecil Menengah (UMKM) Kota Palembang - Annisa Meilani; Isni Andriana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the effect of financial management on the financial performance of small and medium enterprises (MSMEs) in Palembang City. This research uses quantitative methods. The population in this research is food and drink in the city of Palembang so the sample in this study is the entire population of MSMEs in the city Palembang, totaling 75 respondents. The data collection method used in the research was obtained from a questionnaire. Based on the results of hypothesis analysis (t test), it was concluded that Financial Management had a positive and significant effect on Financial Performance in small and medium enterprises (MSMEs) in Palembang City.